The significance of cadmium entering the human food chain via livestock ingestion from the agricultural use of biosolids, with special reference to the UK. (October 2020) - Rigby, Hannah; Smith, Stephen R.
Highlights: Grazing livestock ingest PTEs in biosolids-amended grassland. Ingested Cd does not transfer to muscle tissue in significant concentrations. Cd may accumulate in offal but concentrations are below food limit values. Abstract: When biosolids are applied to agricultural soil, potentially toxic elements (PTEs) accumulate in the topsoil, although it takes many repeated applications to reach soil limit values. Two programmes of UK government-funded research were commissioned in the 1990s to investigate the transfer of PTEs to the food chain via ingestion by sheep grazing biosolids-amended soil. Here, we critically re-examine this evidence in the light of other published work and current food quality standards. This was particularly motivated by the need to determine the safety of biosolids controls on PTEs in relation to revised and stricter European food quality controls for PTEs in foodstuffs. The major pathway for transfer of PTEs to grazing livestock is via direct ingestion of biosolids or biosolids-amended soil from the soil surface. The main elements of concern for the human diet are cadmium (Cd) and lead (Pb), with Cd being the focus of the current paper. Animal ingestion of plant tissue is also a potential pathway for Cd exposure, which, unlike Pb, can transfer to crop tissues. The concentrations of Cd in the muscle tissue of sheep grazing biosolids-amended soil were generally small and similar to control values. Cadmium concentrations in sheep offal were below the maximum permitted concentration for human consumption. This was despite ingestion of soils exceeding the maximum permissible concentration for Cd in soil (3 mg kg −1 dry soil) by up to three times, at an ingestion rate of 10% total dietary dry matter intake. Grazing trials under practical conditions on high Cd soils demonstrated that the Cd concentrations in sheep offal remained below the food limit value for this element in offal from the combined intakes from biosolids-amended soil and herbage. Futhermore, given the substantial fall in environmental emissions and concentrations in biosolids of this element and, consequently, it cannot accumulate in soil to the limit value, biosolids Cd does not represent an issue for the safety of animal meat products.